Building Enduring Capacity for Resilience in the Drylands: Extension Curricula for Livestock Systems - Grossi, Amanda (Bioversity International and the International Center for Tropical Agriculture, 2025)
Presented at IGAD Centre for Pastoral Areas and Livestock Development (ICPALD), the Jameel Observatory for Food Security Early Action and the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) Programme 'Building the Resilience and Prosperity of Pastoralists and Dryland Communities' research and policy dialogue in Nairobi on 1 and 2 October 2025